Haematological Manifestations in Children with Extended Drug-Resistant Salmonella Typhi Infections in a Tertiary Care Hospital - Nazish Tahir; Khattak , Saeed Akhtar Khan; Jamal, Nighat; Shaikh, Ghulam Murtaza; Rabia Ahmad; Waleed Ahmed (Journal of Liaquat University of Medical & Health Sciences, 2024)
OBJECTIVE: To analyze the haematological parameters in children affected by extended drug-resistant salmonella typhi (XDR S. typhi) infections in a Tertiary care hospital. METHODOLOGY: This Descriptive Cross-Sectional study was carried out at the Department of Haematology at PNS SHIFA Hospital, Karachi, from November 2021 to October 2022. Seventy children with XDR S. Typhi on blood culture were selected using a consecutive sampling technique. The study focused on haematological parameters, i.e., haemoglobin (Hb), WBC count, and platelet count. Descriptive statistics were expressed as mean ±SD, and the Chi-square test was applied. A p-value ?0.05 was considered statistically significant. RESULTS: Out of the total of 70 children (under 12 years of age) included in the study, 41 (58.6%) were male and 29 (41.4%) were female. The mean age was 8.17±2.92 years. Anaemia was observed in 51% percent of cases. Leucopenia and thrombocytopenia were noted in 44% and 54% of cases. Seventeen children had bicytopenia, while pancytopenia was seen in only two children. CONCLUSION: XDR S. Typhi infection causes significant cytopenias. Therefore, patients with a history of sustained fever with cytopenias should be worked up for possible XDR S. Typhi infection.